2015
DOI: 10.1186/s12984-015-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of grip force regulation with a low-impedance myoelectric prosthesis featuring referred haptic feedback

Abstract: BackgroundHaptic display technologies are well suited to relay proprioceptive, force, and contact cues from a prosthetic terminal device back to the residual limb and thereby reduce reliance on visual feedback. The ease with which an amputee interprets these haptic cues, however, likely depends on whether their dynamic signal behavior corresponds to expected behaviors—behaviors consonant with a natural limb coupled to the environment. A highly geared motor in a terminal device along with the associated high ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…As explained before, the control interface seemed to be the main limiting factor in the routine grasping task, and therefore, implanted solutions can allow the user to benefit from the higher resolution feedback and thereby improve the control performance. Finally, novel prosthetic devices might be developed allowing fine force control, such as a low-impedance prosthesis presented in [42], which in combination with the better control can also have an important impact on the utility of the feedback.…”
Section: Discussionmentioning
confidence: 99%
“…As explained before, the control interface seemed to be the main limiting factor in the routine grasping task, and therefore, implanted solutions can allow the user to benefit from the higher resolution feedback and thereby improve the control performance. Finally, novel prosthetic devices might be developed allowing fine force control, such as a low-impedance prosthesis presented in [42], which in combination with the better control can also have an important impact on the utility of the feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Not all investigations of haptic feedback in prostheses have resulted in improved functionality. In previous work done by members of our research group, it was found that neither vibrotactile nor jointtorque feedback improved grasp and lift performance over vision with a myoelectric prosthesis [16]. Likewise, Saunders et al found that vibrotactile feedback was only useful in a grasp and lift task with a myoelectric prosthesis when feedforward uncertainty was present in the control loop [26].…”
Section: Task Performancementioning
confidence: 79%
“…Despite these findings, some investigations into the utility of haptic feedback have shown no benefit or improved functionality. In previous research from members of this research group, Brown et al found no significant improvement with either jointtorque feedback or vibrotactile feedback over no feedback in a grasp-and-lift task with a myoelectric prosthesis [16]. Similarly, no significant improvement in myoelectric control was found for a compensatory tracking task with pressure feedback over visual feedback [17].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Intuitive methods to provide somatosensory feedback have been a research topic for several decades [8], and substantial progress was made in recent years [9][10][11][12]. However, a commercially available solution capable of improving the prosthesis performance in the activities of daily living is still unavailable [13,14]. There is a single commercial prosthesis (VINCENTevolution 2, Vincent Systems, DE) equipped with a simple vibratory feedback on the grasping force, but its clinical and functional utility has not been yet demonstrated.…”
Section: Introductionmentioning
confidence: 99%